2019
DOI: 10.1111/jce.14040
|View full text |Cite
|
Sign up to set email alerts
|

Influence of various energy settings and overlap ratios on size and continuity of lesions in a laser balloon ablation in vitro model

Abstract: Introduction: The influence of power (Watt [W]) and total energy (Joule [J]) on lesion size and the optimal overlap ratio remain unclear in laser balloon (LB) ablation for atrial fibrillation. We aimed to evaluate lesion size and visible gaps after LB ablation with various energy settings and different overlap ratios in vitro model. Methods and Results:Chicken muscles were cauterized using the first-generation LB with single applications of full and a half duration of six energy settings (5.5 W/30 seconds [165… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 24 publications
2
35
1
Order By: Relevance
“…We previously reported that overlapped point-by-point laser ablation made lesion depth larger than single-point laser ablation. 17 Therefore, we speculate that overlapped ablation has a synergistic effect with the previous lesion in case that overlapped ablation is performed while local tissue temperature is kept high. Dragging technique is also thought to allow acceptable deep lesion formation by persistent tissue warming (i.e., the effect of temperature stacking), leading to efficient lesion formation.…”
Section: Mechanism Of Lesion Formation By Dragging Lb Ablationmentioning
confidence: 95%
See 3 more Smart Citations
“…We previously reported that overlapped point-by-point laser ablation made lesion depth larger than single-point laser ablation. 17 Therefore, we speculate that overlapped ablation has a synergistic effect with the previous lesion in case that overlapped ablation is performed while local tissue temperature is kept high. Dragging technique is also thought to allow acceptable deep lesion formation by persistent tissue warming (i.e., the effect of temperature stacking), leading to efficient lesion formation.…”
Section: Mechanism Of Lesion Formation By Dragging Lb Ablationmentioning
confidence: 95%
“…This experimental system is similar to that previously described. 17 Commercially obtained chicken breast skeletal muscles were structurally stable even after warming and cutting in the preexperimental study. Therefore, we used them as experimental material.…”
Section: Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Nagase et al and Okishige et al reported that the lesion depth, lesion volume, and maximum lesion diameter increased according to not only the laser output but also the delivered total laser energy in an in vitro model 17,18) . However, our study showed there was no significant difference in the mean output and delivered total energy between the groups with and without PNI.…”
Section: Predictors Of Phrenic Nerve Injury During Vglamentioning
confidence: 99%